2019
DOI: 10.29333/ejmste/109949
|View full text |Cite
|
Sign up to set email alerts
|

Preschool Teachers’ Beliefs and Pedagogical Practices in the Integration of Technology: A Case for Engaging Young Children in Scientific Inquiry

Abstract: This paper presents findings from an on-going international study (Australia and Finland) of preschool teachers' beliefs and pedagogical practices in the integration of technology to engage young children in learning science. Scarcely used in early childhood education research, this study is framed using Mishra and Koehler's (2006) Technological Pedagogical and Content Knowledge (TPACK) theory. Case studies presented in this paper are undertaken with data collected from three preschools in Australia. Participa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 23 publications
(55 reference statements)
1
29
0
1
Order By: Relevance
“…In order to make technology and engineering instruction most useful for early childhood classrooms, we use DBR to intentionally plan open-ended STEMfocused activities that offer children design thinking affordances, specifically developed for young learners. A five step planning process was adapted from (Kewalramani & Havu-nuutinen, 2019) study concerning the essential features of teachers' planning for developing children's STEM-focused inquiry and creativity.…”
Section: Trends and Benefits Of Stem-focused Inquirymentioning
confidence: 99%
See 1 more Smart Citation
“…In order to make technology and engineering instruction most useful for early childhood classrooms, we use DBR to intentionally plan open-ended STEMfocused activities that offer children design thinking affordances, specifically developed for young learners. A five step planning process was adapted from (Kewalramani & Havu-nuutinen, 2019) study concerning the essential features of teachers' planning for developing children's STEM-focused inquiry and creativity.…”
Section: Trends and Benefits Of Stem-focused Inquirymentioning
confidence: 99%
“…The recent shift to a greater societal reliance on technology has mandated that young children's educators emphasize the integration of technology as a play-based manipulative to tune into children's learning and cognitive engagement (Arnott, Palaiologou, & Gray, 2018;Fleer, 2018;Kewalramani & Havu-nuutinen, 2019;. It has been predicted that, due to our rapidly changing technological society, 65 % of the children entering our schools today may have jobs as adults that do not yet exist (Davidson, 2011;Education Council, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…touchscreen devices including iPads) that have become part of young children's everyday experiences (Cao, 2020). Kewalramani and Havu-Nuutinen (2019) provide insights into ways teachers embed digital devices into play-based programs with children under the age of four. From a broader pedagogical perspective, Fleer (2020) analyzes digital pop-up pedagogies, where teachers create a short-term activity with a digital device, and argues that new pedagogies are required to support young children in the technological space.…”
Section: Introductionmentioning
confidence: 99%
“…Although practitioners may be open to change, they remain unconvinced about the use of technology in play (Hatzigianni and Kalaizidis 2018) and do not use their pedagogical skills to support child-initiated learning with technology (Morgan 2010;Vangsnes and Økland 2015). Although research into the use of digital technologies in early childhood education is in its infancy, it has identified that there are many unresolved issues in the effective integration of technology into child-centred learning environments (Kewalramani and Havu-Nuutinen 2019).…”
Section: Introductionmentioning
confidence: 99%